A Comparative Review of Compulsory vs. Optional Mathematics Textbooks: Alignment with Global Standards (Shaheed Smriti Journal, 2025)
Mathematics textbooks play a central role in shaping curriculum implementation and student learning outcomes, particularly in examination-oriented education systems such as Nepal. This study examined the alignment of Grade 9 compulsory and optional mathematics textbooks prescribed in Nepal with internationally recognized mathematics curriculum frameworks. Using a qualitative document analysis approach, the study analyzed official textbooks obtained from the Ministry of Education’s digital library and compared their content against global benchmarks, including the Programme for International Student Assessment (PISA), Trends in International Mathematics and Science Study (TIMSS), the Common Core State Standards for Mathematics (CCSSM), and the National Council of Teachers of Mathematics (NCTM) standards. The analysis focused on content breadth, conceptual depth, cognitive demand, and real-world application. The findings revealed that compulsory mathematics emphasizes foundational procedural skills, whereas optional mathematics introduces greater abstraction and analytical rigor. However, both textbooks demonstrate partial alignment with global standards, particularly in reasoning and mathematical modeling. The study concludes that systematic curriculum refinement is necessary to enhance coherence, depth, and international comparability.